2008
DOI: 10.1089/aid.2008.0180
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Subtype C Drug Resistance among Pediatric and Adult South African Patients Failing Antiretroviral Therapy

Abstract: The emergence of HIV drug resistance is a major obstacle to effective antiretroviral (ARV) treatments. This study examined the drug resistance profiles among South African patients virologically failing ARV therapies between 2000 and 2003, prior to the introduction of a national treatment program. Samples were obtained from 65 HIV-1 subtype C-infected patients (39 children and 26 adults) who had received at least two nucleoside reverse transcriptase inhibitors (NRTIs) and either a nonnucleoside reverse transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
36
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 15 publications
8
36
1
Order By: Relevance
“…This is consistent with the results from many other studies in sub-Saharan Africa, evaluating resistance mutations seen after failure on WHOrecommended first-line ART. [12][13][14][15][16][17][18]20 It has been suggested that where VLs are unavailable and ARV treatment failure is determined using only immunologic and/or clinical criteria-as in much of sub-Saharan Africa-extensive ARV drug resistance is common at the time of line switch. 20 Justifiably, improved access to VLs is advocated for such settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results from many other studies in sub-Saharan Africa, evaluating resistance mutations seen after failure on WHOrecommended first-line ART. [12][13][14][15][16][17][18]20 It has been suggested that where VLs are unavailable and ARV treatment failure is determined using only immunologic and/or clinical criteria-as in much of sub-Saharan Africa-extensive ARV drug resistance is common at the time of line switch. 20 Justifiably, improved access to VLs is advocated for such settings.…”
Section: Discussionmentioning
confidence: 99%
“…Some data show unique patterns of TAMs (hybrid pathways) in HIV-1C in adults in Botswana, 11 whereas data from adults and children in South Africa and other HIV-1C predominant countries show mutations comparable with those found among HIV-1B viruses. 12,13 Most studies of HIV-1C mutations have shown high prevalence of common, low genetic barrier mutations such as M184V and nonnucleoside reverse transcriptase inhibitor (NNRTI). [14][15][16][17][18] However, some have shown considerable prevalence of TAMs and other mutations associated with nucleoside reverse transcriptase inhibitors ([NRTIs] such as K65R, L74V, and Q151M) that can compromise the NRTI backbones used in second-line therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Patient samples (n ϭ 38) from the South African Virological Evaluation (SAVE) study (9) and a workplace HIV program within the mining industry (26) and samples submitted for routine genotyping were selected for resistance phenotyping (27). Samples were selected on the basis of availability and the presence of one or more NNRTI resistance-associated mutations.…”
Section: Hiv-1 Subtype C Sequencesmentioning
confidence: 99%
“…The incidences of K65R in genotyped persons for whom treatment failed were 7%, 9%, 14%, 23%, and 30% in clinical studies in Thailand, Senegal, South Africa, Malawi, and Botswana, respectively (5,7,9,20,21). Tissue culture studies have confirmed that d4T and ddI can select K65R with high efficiency in subtype C viruses (10).…”
mentioning
confidence: 95%